2006
DOI: 10.2334/josnusd.48.239
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric peripheral ossifying fibroma

Abstract: Peripheral ossifying fibroma (POF) is a common solitary gingival growth thought to arise from the periodontal ligament. Though the etiology of POF remains unknown, some investigators consider it an inflammatory or reactive process, while others suggest it is a neoplastic process. In this report, we present and discuss a unique case of multicentric POF, affecting the maxillary and mandibular gingiva of a 49-year-old Caucasian female with meticulous oral hygiene and routine dental care. Though biopsy samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
178
0
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(204 citation statements)
references
References 10 publications
7
178
0
19
Order By: Relevance
“…It is a fairly common lesion, comprising nearly 3% of oral lesions biopsied in one study, approximately 1%-2% in other studies [8][9][10][11]. In 1993, Das and Das obtained similar results, with 1.6% POFs among 2,370 intraoral biopsies [12]. POF may present as a pedunculated nodule, or it may have a broad attachment base [2,5,14].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is a fairly common lesion, comprising nearly 3% of oral lesions biopsied in one study, approximately 1%-2% in other studies [8][9][10][11]. In 1993, Das and Das obtained similar results, with 1.6% POFs among 2,370 intraoral biopsies [12]. POF may present as a pedunculated nodule, or it may have a broad attachment base [2,5,14].…”
Section: Discussionsupporting
confidence: 69%
“…In an isolated case of multicentric POF, Kumar and others noted the presence of a lesion at an edentulous site in a 49-year-old woman, which once again raises questions regarding the pathogenesis of this type of lesion [12]. In the present case it may be due to hormonal influence.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…La gencive qui recouvre la tumeur peut être d'aspect normal ou ulcéré. Généralement, il s'agit d'une lésion isolée, mais un cas de FCOP multicentrique a été rapporté dans la littérature [13]. L'exploration radiographique n'objective, en général, pas de lyse osseuse sous-jacente à la lésion.…”
Section: Commentairesunclassified
“…The lesion was diagnosed to have occurred secondary to a pulpo-periodontal irritation. It has been suggested that a peripheral ossifying fibroma originates from the cells of the periodontal ligament, because, it exclusively occurs in gingival tissues which are close to the periodontal ligaments; oxytalin fibres are often found within the mineralized matrix of the lesion; the age distribution of its occurrence is inversely proportional to the number of permanent teeth which are lost; and the fibrocellular response of a peripheral ossifying fibroma is similar to that of other reactive gingival lesions which originate from the periodontal ligament [6,7].…”
Section: Introductionmentioning
confidence: 99%